Minute torsional reorganization elicited a large visible-range fluorescence gain in terphenyl-derived crystals. (21st January 2022) - Ghosh, Tapan; Mondal, Madalasa; Vijayaraghavan, Ratheesh K.
Abstract : A minuscule structural change of CF3 TP in solid-state impacts the solid-state fluorescence behaviour heavily. A detailed experimental proof for the geometric reorganization upon temperature change or mechanical grinding is described in the manuscript. Abstract : Understanding the variations in the solid-state optical signals of organic semiconductor materials upon subtle structural rearrangement or intermolecular interactions would help to extract the best performance in their electro-optical devices. The significant optical signal gains produced by mild stimuli would be useful to modulate their performance. Thermally or photochemically activated single- and double-bond rotation in the crystalline states is known to yield significant augmentation of their optical output. Herein, we report the cases of a pair of terphenyl derivatives decorated with trifluoromethyl-substituted end groups (CF3 TP ) that exhibit a minuscule molecular structural transformation (a change in the torsional angle) in a polymorphic form, which is reflected in significant visible-range fluorescence augmentation. To understand the underlying mechanism and the effect of the trifluoromethyl groups in CF3 TP, a model compound with methyl substitution (MeTP ) (instead of the trifluoromethyl group) is also described. The photoluminescence (PL) band was entirely in the UV region (with a feeble visible-range overlap) for the freshly prepared sample and, hence, was clearly non-fluorescent under UV illumination. By contrast, the crystalline solids with a slightly modified torsional angle (induced by either grinding, lowering the sample temperature below 160 K or via suitable solvent annealing) resulted in an enhancement of the fluorescence band intensity in the visible range, leading to a deep-blue fluorescent solid. Over 97% enhancement in the visible-range fluorescence was observed for this polymorph. Temperature-dependent single-crystal X-ray analysis coupled with steady-state spectroscopic techniques and picosecond time-resolved PL decay measurements helped to establish the mechanism.